Experience in the Use of Petroleum Emulsion of Сhlorine-Potassium Thermostabilised Inhibited Drilling Solution NEHKT - Deryaev, Annaguly (Anuário do Instituto de Geociências, 2025)
The purpose of this study is to evaluate the effectiveness of the inhibited Neftyanaya Emulsiya Hlorno-Kalievogo Termostabilizirovannogo - inhibited drilling solution - (NEHKT) drilling solution when drilling unstable rocks in red-colour sediments in a certain range of occurrence at a particular well. The study includes preparation of the solution, laboratory tests to determine the optimal components and their proportions, and conducting controlled experiments during which the solution was used in practice. During these tests, the inhibited NEHKT drilling fluid was used in real drilling conditions to evaluate its effectiveness. Conducting controlled experiments allowed evaluating of its ability to prevent complications during the drilling process and the success of the descent and cementing of the production column. The effectiveness of the inhibited NEHKT drilling solution was confirmed under conditions of drilling unstable rocks in red-coloured sediments in the range of 2000-2600 m at well No. 810 of the Nebitdag area. Drilling was also successfully conducted without complications when using the solution, which confirms its ability to ensure the stability of the drilling process and prevent possible problems associated with unstable rocks. The ability of the inhibited NEHKT solution to maintain its structural and mechanical properties in conditions of high mineralisation, penetrate the interplane space of clays, preventing their hydration and swelling, and bind all the water in the solution into persistent hydrates, which contributes to the stability and safety of the drilling process, is identified. Thus, the results of this study indicate the prospects and effectiveness of the inhibited NEHKT drilling solution in the context of ensuring a safe and stable drilling process for unstable rocks in red-coloured sediments.